2021
DOI: 10.1002/sej.1413
|View full text |Cite
|
Sign up to set email alerts
|

From tensions to synergy: Causation and effectuation in the process of venture creation

Abstract: This article examines previously neglected tensions between causation and effectuation in the process of new venture creation. We studied 41 episodes of new venture creation by entrepreneurs in Finland and Denmark, who we followed applying the diary method.We reveal tense relations between the respective causation and effectuation principles at multiple levels, and identify the corresponding mechanisms for their resolution, which, in turn, lead to the synergy. This study enriches the effectuation research by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…Recently, several empirical studies have shown the synergetic effect of causal and effectual logic on venture performance ( Smolka et al, 2018 ; Braun and Sieger, 2021 ; Galkina et al, 2021 ). However, we still know less about how we can get it.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, several empirical studies have shown the synergetic effect of causal and effectual logic on venture performance ( Smolka et al, 2018 ; Braun and Sieger, 2021 ; Galkina et al, 2021 ). However, we still know less about how we can get it.…”
Section: Discussionmentioning
confidence: 99%
“…Causation “takes a particular effect as given and focus on selecting between means to attain this effect” ( Sarasvathy, 2001 , p. 245), which is goal-driven and characteristic of “many-to-one mappings,” effectuation “takes a set of means as given and focus on selecting between possible effects that can be created with that set of means” ( Sarasvathy, 2001 , p. 245), which is non-goal or means driven and characteristic of “one-to-many mappings.” The former prefers to embark on the predictable aspects of an uncertain future, whereas the latter is controllable ( Galkina et al, 2021 ).…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
See 3 more Smart Citations